An evaluation of treatment integrity in a randomised controlled trial of memory rehabilitation for people with multiple sclerosis - Smale, Kathryn J.; Carr, Sara E.; Schwartz, Annette F.; das Nair, Roshan; Lincoln, Nadina B. (SAGE, 2015)
Objective: To assess the treatment integrity of a memory rehabilitation programme for people with multiple sclerosis.